Perancangan Buku Cerita Bergambar “Believe in My Hertz on My Lonely Days” - Dinda Novia Putri; Ariusmedi Ariusmedi (Journal of Creative Student Research, 2023)
This project is proposed as a solution to the lack of illustrated books and education about loneliness. The character of the 52 Hertz whale is featured in this book and represents a depiction of the reality of human life experiencing loneliness. The main goal of this illustrated picture book design is to educate, help people express themselves, prove that those who experiencing loneliness are not alone in facing their problems, and make this book a safe space for them to learn how to manage emotional responses and reduce the risk of depression and loneliness-induced mortality. The method used in this project is the 4D development method, divided into 4 stages: Define, Design, Develop, and Disseminate. Data collection techniques include observation, interviews, literature, and the internet. The data analysis technique used is the 5W + 1H method. In addition to the illustrated picture book, the supporting media produced from this design include postcards, bookmarks, A2 posters, x-banner, hangtag, tote bags, A6 notebook, and cloth banners.